RELIGIONEN UND GEWALT: EIN ESSAY / RELIGIONS AND VIOLENCE: AN ESSAY - Michael Amaladoss, S. J. (Caminhos)
The essay presupposes interreligious violence as a daily phenomenon in the world. It attributes to the religions themselves the responsibility of this reality. At the same time it claims that these same religions also have the potential to contribute to peace and its construction. The focus of its attention is on the Middle East, highlighting religious identity, community, and religious fundamentalism as matrices of this ambiguity. It also focuses its attention on the religious realities in Sri Lanka, characterizing the significance of the religions present there. It concludes that, beyond differences, disputes and hostilities, religions can (re)discover and empower themselves in the works for dialogue, communion, justice and world peace.